The Writing of Hadith in the Era of Prophet Muhammad: A Critique on Harun Nasution’s Thought - Daud Rasyid Harun; Aisyah Daud Rasyid; Asmuliadi Lubis; Mohd Abd Wahab Fatoni Bin Mohd Balwi; Bilal Daud Rasyid (Al-Jami'ah: Journal of Islamic Studies, 2021)
The discussion regarding the writing of hadith during the life of the Prophet is a contentious topic within the area of Islamic and hadith studies both in the West and in the Islamic world. Orientalists write their work on hadith with a presumption that hadith has never been written during the life of Prophet Muḥammad. They contend that hadith text only emerged in the third century of Hijrah, i.e. in the era of al-Bukhāri. A few others believe that it started in the era of Malik of the Umayyad. This orientalist’ mindset affects some Muslim intellectuals who accept this premise. One of them is Harun Nasution, a well respected great mind who wrote a book entitled Islam Ditinjau Dari Berbagai Aspeknya (Islam Viewed from Various Aspects). However, historical evidence demonstrates that the writing of hadith was carried out at the time when the Prophet was still alive. A number of sheets were discovered, which contain hadith text compilations narrated by the companions of the Prophet, such as the Ṣahīfah of  ͑Ali bin Abi Ṭalib, Ṣahifah of Jābir bin  ͑Abdillah, and others. Some scholars have misunderstood the message in a saying of the Prophet that prohibited the writing of hadith. They have ignored other hadith that negated the previous hadith by which the Prophet allowed the writing of hadith in his life time. Even though there are a number companions who did not write hadith in this period, it does not mean hadith were not allowed to be written, but it was due to their own preference not to write the hadith.[Perdebatan tentang penulisan hadits masa kehidupan Nabi tetap menjadi tema yang hangat dalam kajian keislaman dan kajian hadits, baik di barat maupun di dunia Islam sendiri. Beberapa orientalis berpendapat bahwa hadits tidak ditulis pada masa Nabi Muhammad. Mereka menyebutkan teks hadits mulai muncul abad ketiga hijriah, misalnya pada era Bukhari. Lainnya percaya bahwa teks hadits dimulai pada masa Malik al Umayyad. Perspektif seperti orientalis ini diterima oleh beberapa intelektual muslim Indonesia, salah satunya Harun Nasution yang menulis buku Islam ditinjau dari Berbagai Aspeknya. Bagaimanapun bukti sejarah menunjukkan penulisan hadits sudah dimulai ketika Nabi masih hidup. Sejumlah lembaran yang mengandung kompilasi teks hadits dari beberapa sahabat Nabi seperti, Ṣahīfah dari Ali bin Abi Ṭalib dan Ṣahifah dari Jābir bin  ͑Abdillah. Sejumlah akademisi keliru dalam memahami pesan Nabi yang melarang menuliskan hadits. Mereka mengabaikan hadits yang menegasikan hadits sebelumnya yang membolehkan penulisan hadits selama hidup Nabi. Meskipun ada sejumlah sahabat yang melarangnya, namun ini bukan berarti hadits tidak diijinkan untuk ditulis, tetapi hal ini lebih terkait dengan masing-masing referensi untuk tidak menuliskannya.]